PENGARUH PEMBERIAN SILASE BATANG PISANG (Musa paradisiaca) TERHADAP KONSUMSI DAN PERTUMBUHAN DOMBA EKOR GEMUK JANTAN: THE EFFECT OF FEEDING BANANA STICKS (Musa paradisiaca) SILAGE ON CONSUMPTION AND GROWTH OF MALE FAT TAILED SHEEP - Desi Yuli Setyono; Suhardi Suhardi; Purwadi Purwadi (Universitas Boyolali, 2022)
This research aims to know the influence of the silage of the banana rod against the consumption and growth of the Jantan Fat Tail Sheep. This research uses 16 poultry lamb tails with an average of 16,5±3,35 kg (CV=20%). The design used is Complete Random Design (RAL) with 2 treatments and 8 repeats, ‘t’ test data analysis forward . Ration provided is a Concentrate (callfeed®) and a banana rod silage. The treatment given is T0 (60 % pennisetrum grass + 40 % concentrate) and T1 ( 60 % pennisetrum grass + 40 % banana rod silage). The result of statistical analysis leads to the use of the silage of the banana stems is significant (P<0.01) against Feed Consumption, Dry Material Consumption, Crude Protein Consumption (PK), Feed Conversion., and significant (P<0,05) against to daily gain and feed cost per gain. Conclusion of this research are used of silage banana stem can increase the consumption and growth of Sheep.